Healthy Lifestyles Associated With Socioeconomic Determinants in the Older Adult Population - Elizabeth Roldán González; Piedad Rocio Lerma Castaño; Adriana Yulieth Aranda Zemanate; Ángela Giovana Caicedo Muñoz; Gisella Bonilla Santos (SAGE Publishing, 2022)
Introduction/Objective: The evaluation of lifestyle in older adults and the study of socioeconomic determinants becomes an essential indicator of the health conditions of older adults. The purpose of this study was to establish the relationship between socioeconomic factors and healthy lifestyles in older adults. Methods: Study with a quantitative approach, descriptive type, non-experimental design, cross-sectional in a sample of 407 elderlies who have applied a self-designed instrument for socioeconomic characterization and the FANTASTIC test to assess lifestyle. For data analysis, a bivariate analysis was applied using chi2 and multivariate analysis using ordinal logistic regression. Results: 53% of elderlies aged between 60 and 70 years reported their lifestyle as excellent and very good. Age, average household income, and perceived health status are associated with healthy lifestyles in older adults. Conclusions: This study found that in addition to socioeconomic determinants, self-perceived health is a factor that influences the lifestyles of this population.